2007
DOI: 10.1111/j.1365-2044.2007.04953.x
|View full text |Cite
|
Sign up to set email alerts
|

Cost evaluation in the intensive care units of Trinidad applying the cost‐blocks method – an international comparison*

Abstract: SummaryThis study evaluated the costs of intensive care in Trinidad applying the cost-blocks method. Data regarding demographics, severity of illness, therapeutic interventions and length of stay were prospectively recorded for 111 patients admitted to four intensive care units during a 3-month period. Annual costs, cost per admission, cost per patient-day and cost per therapeutic intervention score point were derived. The cost-block for staff, especially medical staff, was the largest proportion of the expend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
2
0
2
Order By: Relevance
“…Although, the total ICU costs may provide a rough estimate of the resource consumption in ICU as a proportion of the total hospital budget, specific data on the cost of ICU care e.g., for survivors versus nonsurvivors, and the association of costs with the severity of illnesses of patients may be important, especially to implement quality improvement measures such as ICU admission protocols. The mean cost of ICU care per patient in Trinidad & Tobago was US$ 5228 as reported in a previous study published in 2007 [8]; however, there was no comparison of costs between survivors and non-survivors. A study done in Barbados showed the cost of ICU admission to be US$ 6818, which also compared the costs for survivors (US$ 6134) to non-survivors (US$ 10445) [9].…”
Section: Introductionmentioning
confidence: 73%
“…Although, the total ICU costs may provide a rough estimate of the resource consumption in ICU as a proportion of the total hospital budget, specific data on the cost of ICU care e.g., for survivors versus nonsurvivors, and the association of costs with the severity of illnesses of patients may be important, especially to implement quality improvement measures such as ICU admission protocols. The mean cost of ICU care per patient in Trinidad & Tobago was US$ 5228 as reported in a previous study published in 2007 [8]; however, there was no comparison of costs between survivors and non-survivors. A study done in Barbados showed the cost of ICU admission to be US$ 6818, which also compared the costs for survivors (US$ 6134) to non-survivors (US$ 10445) [9].…”
Section: Introductionmentioning
confidence: 73%
“…Beispiele hierfür sind die Intensivstationen und das Mammografie-Screening. Die Hçhe der erforderlichen Ressourcen, die für Intensivstationen ausgegeben werden müssen, um ein Leben zu retten, ist unter dem Aspekt der technischen Effizienz nicht zu verantworten [10,11,13,23]. Würden die çkonomischen Grenzen von kosteneffektiven Gesundheitsleistungen angelegt, dürften keine Intensivstationen mehr finanziert werden.…”
Section: Die Technische Die Allokative Und Die Globale Effizienzunclassified
“…Recently, there has been an increased need for intensive care units (ICU) owing to aggressive therapeutic interventions for critically ill patients (Barbieri et al, 2003). Critical care is one of healthcare's high-technology and high-budget areas, and most countries strive hard to cope with increasing demand for ICU facilities (Hariharan et al, 2007). On one hand, ICU availability may be the primary issue (especially in the developing world); while on the other, unit performance is a wider global issue.…”
Section: Introductionmentioning
confidence: 99%